Une ville d’Abitibi : Senneterre - Biays, Pierre (Cahiers de géographie du Québec, 1957)
Senneterre is a typical pioneer town in the Abitibi region. The main factor of development of Senneterre is its location in connection with the previously built railroads, new railroads and railroads to be built which are linking the settled part of Abitibi and Northern Ontario as well as the Montréal and Québec regions with the new mining and forestry districts of Bachelor, Chibougamau and Albanel lakes. In addition, sawmills and C.N.R. repair and maintenance shops are important industries in Senneterre.